Trends in pharmacy-based dispensing of buprenorphine, extended-release naltrexone, and naloxone during the COVID-19 pandemic by age and sex – United States, March 2019 – December 2020. (1st March 2022) - Cremer, Laura J.; Board, Amy; Guy, Gery P.; Schieber, Lyna; Asher, Alice; Parker, Erin M.
Abstract: Background: COVID-19 stay-at-home orders may reduce access to substance use treatment and naloxone, an opioid overdose reversal drug. The objective of this analysis was to compare monthly trends in pharmacy-based dispensing rates of medications for opioid use disorder (MOUD) (buprenorphine and extended-release [ER] naltrexone) and naloxone in the United States during March 2019–December 2020 by age and sex. Methods: We calculated monthly prescription dispensing rates per 100, 000 persons using IQVIA New to Brand. We used Joinpoint regression to calculate monthly percent change in dispensing rates and Wilcoxon Rank Sum tests to examine differences in median monthly rates overall, and by age and sex between March 2019–December 2019 and March 2020–December 2020. Results: Buprenorphine dispensing increased among those aged 40–64 years and ≥ 65 years from March 2019 to December 2020. Median rates of total ER naltrexone dispensing were lower in March 2020–December 2020 compared to March 2019–December 2019 for the total population, and for females and males. From March 2019 to December 2020, ER naltrexone dispensing decreased and naloxone dispensing increased for those aged 20–39 years. Conclusions: Dispensing ER naltrexone declined during the study period. Given the increase in substance use during the COVID-19 pandemic, maintaining equivalent access to MOUD may not be adequate to accommodate rising numbers of new patients with opioid use disorder. Access to all MOUD and naloxone could be further expanded to meet potential needs during and after the public health emergency, given their importance in preventing opioid overdose-related harms. Highlights: Declines in extended-release naltrexone dispensing may indicate reduced access. Despite increases in buprenorphine and naloxone, there may not be adequate access. Expanding treatment access is crucial during and after the pandemic. There are several policies, such as telehealth, that can help increase access.